HUBUNGAN KEMANDIRIAN BELAJAR DENGAN HASIL BELAJAR PESERTA DIDIK KELAS VIII SMP N 14 KABUPATEN TEBO - Ilham Setiawan ilham (LPPM Universitas Muhammadiyah Muara Bungo, 2019)
The level of success of students in the learning process is expressed by the learning outcomes. Learning outcomes are expressed as learning success rates expressed in the form of scores, after the learning process. Learning outcomes achieved by students give an overview of their level of position compared to other students. To find out someone has undergone a learning process and has undergone changes, both changes in knowledge, skills or attitudes can be seen from the learning outcomes.